The influence of psychological determinants and retirement planning on perceived bridge employment: examining the moderating effect of job satisfaction among employees in Sabah / Zaiton Osman - Osman, Zaiton (Institute of Graduate Studies, UiTM, 2015)
Retirement forces older workers to disconnect with their previous behavioural patterns and economic position. Transition and adjustment from working life to retirement places great psychological pressure and financial distress on older workers, especially those with dependent children. Bridge employment provides a solution for older workers to continue working after retirement while transitioning into retirement slowly and smoothly. As losing the job role has a significant impact on the psychological well-being of retirees, engaging in bridge employment helps to fulfil the important psychological functions of older workers by providing an adaptive style to retirement. This study investigates the influence of psychological determinants (future time perspective, retirement goal clarity and financial knowledge) and retirement planning on bridge employment. Moreover this study also examines the moderating effect of job satisfaction among employees in Sabah. Retiring individuals must adapt and make major life transitions. A self-administered questionnaire was used in this study and a total of 523 samples were collected for nine major district in Sabah…